Pilot study on depression among secondary school students in Selangor - S., Adlina; Ariaratnam, Suthahar; Musa, Ramli; AB, Edariah; Aye, Soe-Soe; F., Mohd Ariff; AHH, Narimah; AS, Nuraliza; C., Karuthan (Malaysian Medical Associations, 2007)
A cross sectional descriptive study of 2048 subjects was conducted to determine the prevalence of depression and factors influencing depression among students in secondary school from urban and rural areas in the state of Selangor. Malaysia. The children's depression inventory (COl) developed by Maria Kovacs was used in this study. Students who participated in this study come from two urban schools and three rural schools. It was found that in the yield for scores for five factors were 9.2% have negative mood. 5% have interpersonal problems. 8.3% have ineffectiveness. 9.8% have anhedonia and 10.6% have negative self esteem. Following the interpretive guidelines for the T-scores. it was found that 10.3% of the students were much above average in the depression scale. This study also found that: 1% of students were smoking. 1.6% of students were gum sniffling. 0.9% took drugs. 4.1 % took alcohol and 9.9% took things from other people. Females were more depressed than males. The Chinese students were more depressed compared to Indian students. Students whose parents had no formal education or had only primary education were more depressed than students whose parents had secondary. college or university education. Depression increased with increasing number of siblings. Depression contributed to the habit of drug abuse. gum sniffing and stealing but not to smoking and alcohol abuse. Suicidal tendencies were more likely among the depressed students. It is imperative that not only caregivers but also teachers have to be equipped with the knowledge. attitude and skills to assist secondary school children cope with their emotions. handle conflicts and manage stress early so that a more productive society will develop in the future.